Listen right bags silver medal - Runggol, Christine Jacqueline; Lau, Kimberley (UiTM Sarawak, 2024)
UiTM Perlis organised the International Innovation Competition on Languages, Education and Societies (IINNCOME2022). The competition with its theme, ‘Humanising Learning, Teaching and Societies in Digitalised Contexts’ was held from 31st January 2022 to 8 July 2022. The objectives of the programme were to nurture innovation culture among students, language educators, and practitioners at secondary and tertiary level, as well as communities and industries. Participants were required to submit an innovation video of teaching and learning idea or product either in group or individually. Many inventions and innovations from various fields were showcased during the competition.